Positive maternal mental health in pregnant women and its association with obstetric and psychosocial factors - Álvaro Monterrosa-Castro; Shairine Romero-Martínez; Angélica Monterrosa-Blanco (BMC, 2023)
Abstract Objective To estimate the frequency of Positive Maternal Mental Health (PMMH) interpretation levels in pregnant women who attended prenatal consultation and to identify their association with obstetric and psychosocial factors. Methods A cross-sectional study that included pregnant women who attended prenatal care at 12 or more weeks of gestation. The following scales were applied: Positive Mental Health Questionnaire (PMHQ), Goldberg Anxiety and Depression Scale, and Jong Gierveld Loneliness Scale. Results 702 pregnant women were evaluated; 634 (90.3%) had flourishing PMMH, and 68 (9.7%) had non-flourishing PMMH. Among the latter, all were at an intermediate level, and none were languishing. Flourishing PMMH was more frequent in adults (91.2%) compared to adolescents (75.0%) and in women with higher education (93.0%) than in those with basic education (83.9%). The PMHQ factors and global score correlated positively with maternal age and negatively with anxiety, depression, emotional, social, and general loneliness. Associated with a higher frequency of non-flourishing PMMH were general loneliness OR:6.32[CI95%:3.38-11.82], social loneliness OR:5.98[CI95%:3.42-10.42], adolescence OR:3.47[CI95%:1.61-7.45], emotional loneliness OR:3.12[1.83-5.32], anxiety OR:2.14[CI95%:1.27-3.60], and depression OR:1.88[CI95%:1.09-3.25]. Less frequently: work occupation outside the home OR:0.41[CI95%:0.24-0.68], technical/technological studies OR:0.22[CI95%:0.08-0.60] and university OR:0.27[CI95%:0.10-0.71]. Preconception consultation, desired pregnancy, cesarean section, and fetal or neonatal death were not associated. In the adjusted model: general loneliness OR:3.02[CI95%:1.10-8.31], social loneliness OR:2.82[CI95%:1.38-5.79] and anxiety OR:1.93[CI95%:1.02-3.67], retained statistical significance. Conclusion Nine out of ten pregnant women had flourishing PMMH, and none had languishing PMMH. None of the obstetric factors were associated with non-flourishing PMMH but with general loneliness, social loneliness, and anxiety.